The Enlightenment a very short introduction - Robertson, John 1951- (Very short introductions, 2015)
This introduction explores the history of the 18th-century Enlightenment movement. Considering its intellectual commitments, Robertson then turns to their impact on society, and the ways in which Enlightenment thinkers sought to further the goal of human betterment, by promoting economic improvement and civil and political justice